Atividades antimicrobiana e antipromastigota de extratos e frações de Virola surinamensis (Rol ex Rottb.) Warb (Myristicaceae) - SARAIVA, Maria Elinete Veras (Universidade Federal do Pará, 2015)
The present study aimed to evaluate the antimicrobial activity of extracts and antipromastigota V. surinamensis and its fractions. To obtain the extracts have been used increasingly polar solvents (hexane, ethyl acetate and methanol) and the ethyl acetate extract was fractionated into open column chromatography, using as stationary phase silica gel and eluents such as mixtures of hexane and ethyl acetate gradient increasing polarity. To evaluate the antimicrobial activity was used in agar diffusion test being used the following microorganisms: Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa and Candida albicans. The active fraction was subjected to microdilution, which determined the minimum inhibitory concentration (MIC). In assessing the activity antipromastigota used the Leishmania amazonensis and L. chagasi, being determined the minimum inhibitory concentrations and 50% inhibitory concentration (IC50). Extracts hexane, ethyl acetate and methanol were subjected to agar diffusion test, and there were no inhibitions of bacterial and fungal growth. Just FA3 ethyl acetate fraction obtained from the ethyl acetate extract inhibited the growth of S. aureus in the agar diffusion test. But in this fraction microdilution proved inactive (MIC> 1000μg / mL). Only the hexane extract was active in promastigote forms of L. amazonensis and L.chagasi. In short, only the hexane extract was active in promastigote forms of Leishmania.